Certainty Law For Health Workers In Health Services - Iyo Iko Rasaki; Yasmirah Mandasari Saragih; Marice Simarmata (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Health services aim to maintain and improve the quality of health, as well as prevent and treat diseases in the community.This study aiming to analyze the legal certainty for health workers in health services, using the normative legal method. The data source comes from a literature review. The results of this study indicate that Law Number 17 of 2023 regarding Health brings significant changes to the legal certainty for health workers in Indonesia in terms of health services. Previously, legal certainty for health workers was spread across various separate laws. However, with the enactment of Law Number 17 of 2023, this legal protection has become more integrated and comprehensive. Updates regarding the protection of health workers include increasing the rights of health workers, including affirmation of compliance with professional standards and ethics. There are improvements in rights, salary, performance allowances, health insurance, and opportunities for self development. This protection is strengthened by giving health workers the authority to stop services if there is a violation of ethics. It is necessary to strengthen operational procedures and work standards that can be a reference for health workers in carrying out their duties, thereby reduce the risk of negligence that can result in criminal sanctions and additional regulations are also needed to ensure a fair legal mechanism for health workers in facing accusations of negligence, by considering ethics and professional aspects in their work.